Celocentesis for early prenatal diagnosis of hemoglobinopathy. (13th October 2020) - Makrydimas, G.; Damiani, G.; Jakil, C.; Cigna, V.; Orlandi, M.; Picciotto, F.; Schillaci, G.; Cassarà, F.; Vinciguerra, M.; Leto, F.; Giambona, A.; Maggio, A.; et al.
ABSTRACT: Objective: Celocentesis is an invasive technique that can provide prenatal diagnosis of single‐gene disorders, from as early as 7 weeks' gestation. The objective of this study was to examine the safety of celocentesis. Methods: In this prospective study, celocentesis was performed for prenatal diagnosis of hemoglobinopathy in 402 singleton pregnancies in which both parents were carriers of β ‐thalassemia or sickle cell disease trait. We assessed procedure‐related maternal discomfort or pain, success of sampling and obtaining results, pregnancy outcome and postnatal follow‐up. Results: First, celocentesis was carried out at a median gestational age of 8.6 (range, 6.9–9.9) weeks and celomic fluid was successfully aspirated in 99.8% of cases. Second, 67% of women had no or only mild discomfort, 18% had moderate discomfort, 12% had mild‐to‐moderate pain and 3% had severe pain. Third, prenatal diagnosis from analysis of the celomic fluid was successful in 93.8% cases, and in the last 121 cases, it was always successful. Fourth, in all cases of successful sampling and analysis of celomic fluid, the diagnosis was concordant with results obtained from additional prenatal or postnatal testing. Fifth, in addition to diagnosis of hemoglobinopathy, quantitative fluorescence polymerase chain reaction analysis, which was performed to evaluate maternal contamination using several markers for chromosomes X, Y, 21, 18 and 13, led to the accurate diagnosis of chromosomal aneuploidy. Sixth, in all cases of an affected fetus diagnosed by celocentesis in which the parents chose termination of pregnancy, this was carried out < 10 weeks' gestation. Seventh, in 97.1% (298/307) of the continuing pregnancies there was live birth, in seven (2.3%) there was miscarriage and in two (0.7%) there was loss to follow‐up. Eighth, fetal abnormalities were diagnosed in three (1%) cases, including unilateral transverse amputation of the forearm, unilateral moderate hydronephrosis and small‐bowel duplication. All neonates were examined by a pediatrician and were found to be phenotypically normal, except for the three cases with a prenatally diagnosed defect. Conclusions: Celocentesis can be used for early prenatal diagnosis of genetic abnormalities, and the procedure‐related risk of pregnancy complications appears to be low. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked article: There is a comment on this article by Li and Li. Click here to view the Correspondence.